Aberrant MUC1 accumulation in salivary glands of Sjögren's syndrome patients is reversed by TUDCA in vitro. (3rd August 2019) - Castro, Isabel; Albornoz, Nicolás; Aguilera, Sergio; Barrera, María-José; González, Sergio; Núñez, Matilde; Carvajal, Patricia; Jara, Daniela; Lagos, Carolina; Molina, Claudio; Urzúa, Ulises; Hermoso, Marcela A; et al.
Abstract: Objectives: Xerostomia in SS patients has been associated with low quality and quantity of salivary mucins, which are fundamental for the hydration and protection of the oral mucosa. The aim of this study was to evaluate if cytokines induce aberrant mucin expression and whether tauroursodeoxycholic acid (TUDCA) is able to counteract such an anomaly. Methods: Labial salivary glands from 16 SS patients and 15 control subjects, as well as 3D acini or human submandibular gland cells stimulated with TNF-α or IFN-γ and co-incubated with TUDCA, were analysed. mRNA and protein levels of Mucin 1 (MUC1) and MUC7 were determined by RT-qPCR and western blot, respectively. Co-immunoprecipitation and immunofluorescence assays for mucins and GRP78 [an endoplasmic reticulum (ER)-resident protein] were also performed. mRNA levels of RelA/p65 (nuclear factor-κB subunit), TNF-α, IL-1β, IL-6, SEL1L and EDEM1 were determined by RT-qPCR, and RelA/p65 localization was evaluated by immunofluorescence. Results: MUC1 is overexpressed and accumulated in the ER of labial salivary gland from SS patients, while MUC7 accumulates throughout the cytoplasm of acinar cells; however, MUC1, but not MUC7, co-precipitated with GRP78. TUDCA diminished the overexpression and aberrant accumulation of MUC1 induced by TNF-α and IFN-γ, as well as the nuclear translocation of RelA/p65, together with the expression of inflammatory and ER stress markers in 3D acini. Conclusion: Chronic inflammation alters the secretory process of MUC1, inducing ER stress and affecting the quality of saliva in SS patients. TUDCA showed anti-inflammatory properties decreasing aberrant MUC1 accumulation. Further studies are necessary to evaluate the potential therapeutic effect of TUDCA in restoring glandular homeostasis in SS patients.